1993
DOI: 10.1111/j.1755-3768.1993.tb04619.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal tension glaucoma: The value of predictive tests

Abstract: Fifty-four normal tension glaucoma cases were studied to determine the value of several clinical tests for predicting the progression of the disease. Outflow facility, intraocular pressure (IOP) increase after water drinking, and diurnal changes in IOP were studied. Progression was determined on the basis of changes in visual sensitivity as measured on the Octopus 201. A minimum of four examinations of the central 30 degrees were conducted over a 3- to 7-year period. Progression of visual field defects was see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…In this study, we analyzed the relationship between IOP variability, which may be divided into IOP peak and IOP fluctuation, and CCT. Intraocular pressure peaks are not always obtained in office hours but are usually seen either in a 24‐hour tension curve, as shown by Drance,7 or in the WDT, as demonstrated by other authors 5,18,19. This is the reason ophthalmologists should not perform just a single IOP measurement during office hours.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we analyzed the relationship between IOP variability, which may be divided into IOP peak and IOP fluctuation, and CCT. Intraocular pressure peaks are not always obtained in office hours but are usually seen either in a 24‐hour tension curve, as shown by Drance,7 or in the WDT, as demonstrated by other authors 5,18,19. This is the reason ophthalmologists should not perform just a single IOP measurement during office hours.…”
Section: Discussionmentioning
confidence: 98%
“…Filtration 17,126 The authors found that the diurnal IOP peak was higher and the IOP fluctuation was greater in the medically treated group. The same pattern in IOP peak and fluctuation was seen after the WDT.…”
Section: Circadian Iop Variations In Treated Eyesmentioning
confidence: 99%
“…The WDT, popular in the 1950s and 1960s, was later discarded as a diagnostic tool for open-angle glaucoma because of low sensitivity and specificity 7 8. In recent years, the WDT has been identified as a reliable and safe tool to predict maximum IOP values during a diurnal tension curve (DTC) and to assess the patency of surgical interventions 911…”
mentioning
confidence: 99%